MORATORIUM ON LAND - Kozlova, Tetyana; Kryachek, Vladislav (Proceedings of National Aviation University (archive), 2014)
The negative effects of extending the moratorium on the sale of agricultural land are considered. The main sellers of land under the moratorium are highlighted in the article. The necessity of lifting the moratorium is proposed. A scheme to overcome the moratorium on the sale of agricultural land is proposed and analyzed.